2020
DOI: 10.1002/cta.2843
|View full text |Cite
|
Sign up to set email alerts
|

Four‐phase interleaved DC–DC step‐down converter using coupled inductor for high power application

Abstract: The objective of this manuscript is to analyze and design a new interleaved dc-dc buck-type converter based on the conventional interleaved topologies. The proposed converter consists of small size filters, few component numbers, and low current and voltage ripple compared with interleaved dc-dc converter family. Furthermore, detailed comparisons are made concerning the operating mode, the component numbers, dc voltage gain, voltage stresses, output inductor current ripple, rated power, and efficiency. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The DC voltage gain can be calculated using the following expression for the case of two phases (43), and for the case of three phases (44) [18]:…”
Section: DC Voltage Gain In Buck Modementioning
confidence: 99%
“…The DC voltage gain can be calculated using the following expression for the case of two phases (43), and for the case of three phases (44) [18]:…”
Section: DC Voltage Gain In Buck Modementioning
confidence: 99%
“…Additionally, 59 can become 60, if parasitic resistances are not into account. Thus, it can be identified that the ideal voltage gain is the same as 21 GitalicBuckitalicIPWMgoodbreak=VitalicBFEVitalicPCCgoodbreak=40.12emDLIRLoad20.12emRLoad+2RL1()4DLI2goodbreak−3DLIgoodbreak+1+RS1()4DLI2goodbreak−2DLIgoodbreak+1 GitalicBuckitalicIPWMgoodbreak=VitalicBFEVitalicPCCgoodbreak=20.12emDLI Figure 12 shows the plot of 56, 57, 59, and 60 considering several values of load resistance, including the parasitic resistance values presented in Table 1.…”
Section: Continuous Conduction Mode (Ccm) Operation Analysismentioning
confidence: 99%
“…Here, a detailed procedure is given for voltage gain, design consideration, and stress across semiconductors, and efficiency is consolidated. Furthermore, another review is presented in DivyaNavamani et al, 3 which focuses on the bidirectional operation of the converter with the control and stability issues using amplitude and phase plots in different cases 4 . Study aims to optimize wide input range and high‐gain DC‐DC boost converter designs for FCVs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, another review is presented in DivyaNavamani et al, 3 which focuses on the bidirectional operation of the converter with the control and stability issues using amplitude and phase plots in different cases. 4 Study aims to optimize wide input range and high-gain DC-DC boost converter designs for FCVs. It reviews research on impedance network-based converters, evaluates using eight criteria, discusses FCV converter challenges, and proposes future research directions.…”
mentioning
confidence: 99%